Meniere’s Disease: New Frontiers in Management for Better Results - Velusamy, Anand; Anand, Aiswarya; Janarthanan, Sridurga (Annals of Otology and Neurotology, 2020)
Introduction Meniere's disease (MD) remains a difficult disease to diagnose, especially in the early stages when not all of the symptoms may be present. Sensorineural hearing loss, tinnitus, and recurrent vertigo constitute the hallmark symptoms of MD. Endolymphatic hydrops (EH) has been described as the responsible pathology in MD. Since that description, the medical and surgical treatment of MD have been directed at reducing the volume of endolymph. Unfortunately, these approaches have had equivocal success in the control of vertigo and recovery of hearing. So, a routine treatment directed at resolution of EH may not be suitable for all patients. Treatment has to be directed at the cause of EH whenever possible.Objectives The aim of this study was to define new findings in clinical tests and modes of treatment in MD, to determine the outcome of vertigo and hearing in patients after treatment, and to describe treatment which will prevent long term deterioration of hearing.Materials and Methods Forty-six new patients with a diagnosis of MD were treated with antiviral drugs or diuretics. Drugs were used based on nature of dehydration test. Hearing test including pure tone average (PTA) and speech discrimination (SD) was performed prior to treatment and at 1 to 2 months, 6 months, and 1 year after initiation of treatment. Effect on dizziness was recorded at each evaluation; hearing was judged to be improved, if PTA was lowered by at least 10 to 15 dB or an increase in SD > 20%.Results The antiviral approach has virtually eliminated the use of various surgical methods used in the past. Dehydration test-based treatment protocol with diuretics and antivirals and antimigraine prophylaxis when needed has led to remission of disease in 93.5% of patients. With prompt treatment, inner ear damage can be prevented.Conclusion Orally administered antiviral drugs should be considered in the treatment of MD. Migraine-associated MD patients need migraine prophylaxis and this will lead to improvement in Meniere’s symptoms also. If Intratympanic therapy is considered, then targeted low-dose delivery method of using Gelfoam instillation of gentamicin is preferable according to our study to prevent any significant hearing loss.
Keywords: antivirals; balance diseases; dehydration test; intratympanic treatment; migraine